DETERMINANTS OF DIVERSIFICATION OF INCOME SOURCE AMONG RURAL FARMING HOUSEHOLDS IN OYO STATE, NIGERIA - A. S., COSTER; O.L, BALOGUN; M.I, ADEKOYA (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2021)
In sub-Saharan Africa, reliance on agriculture tends to diminish continuously as income level rises. Diversification of income sources is the livelihood strategies households employed to minimize household income variability. This study investigated the determinants of diversification of income among rural farming households in Oyo state, using data from a cross sectional survey of 120 farming households. Data were analyzed using descriptive statistics, Inverse Herfindahl-Hirschman Diversity (IHHD) index and Probit regression model. Results showed that 55.3% of the sample respondents were male with an average age of 42 years and an average of 10 years of farming experience and educational level respectively. Result of IHHD showed that 73.3% of the sample households in the study area had diversified income sources. It was found that agriculture still remains the major source of rural income for the farmers with 60% of the farmers derived their income from arable crop farming and 37.5% from livestock production. Among the non-farm income source, Okada riding (48.3%) and artisanal (33.3%) were the prevalent income generating activities. Similarly, in the off-farm categories, marketing of farm produce (41.2%) and collection of firewood and charcoal (30%) were the dominant income generating activities. During the period, an average income of ₦68,979.50 was earned from on-farm activities while ₦55,852.77 and ₦33,465.52 were earned from non-farm and off-farm activities respectively. Results revealed that the age and education level of household head, household size, farm size and ownership of assets were the relevant and significant factors that influenced the likelihood of income diversification among rural farming household.